TEACHER BEHAVIOR STRATEGY IN THE UNCERTAINTY OF THE CONDITIONS OF PROFESSIONAL DEVELOPMENT - Naumova, Viktoriia (Educological discourse, 2020)
It is proved that the current tendencies of reforming the postgraduate pedagogical education make it possible to state that the uncertainty in obtaining the results of professional development of teachers is the main condition for the emergence of risks of professional development. The concept of professional development in terms of the paradigm of education is characterized. An experimental research was organized and conducted. The purpose was to determine the personal properties of teachers, which determine the effectiveness of decision-making in a situation of uncertain of the conditions of professional development. The objectives of the experiment include: to establish the professional and personal qualities of teachers, which make decision-making in a situation of uncertainty; perform mathematical processing and interpretation of experimental research; summarize the results and make recommendations. This research presents results of definition and substantiation of the main strategies of behavior of teachers in the situation of uncertain conditions of professional development. These include: vigilance, avoidance, procrastination, dustiness. Teachers have the highest average values for the Vigilance Strategy, which indicates a careful consideration of alternatives before making a decision. The generalized results of the research characterize the educators’ conscious choice of a behavioral strategy to make a decision in a situation of uncertain conditions of professional development. It is established that modern postgraduate pedagogical education has various forms of formal, non-formal and informal adult education. In the long term, we consider it necessary to analyze the potential of technologies of professional development of teachers in terms of advanced training.